Sort by

- Relevance
- |Time

(1+

**r**/m)^m (1+1/(m/**r**))^m (1+1/(m/**r**))^mr/**r**(1+1/(m/**r**))^**r**(m/**r**) as m -> infin, so does m/**r**(1+1/(m/**r**))^**r**(m/**r**) This is e^**r**Lets evaluate the limit mathematically...3 Answers · Science & Mathematics · 03/12/2008

**R**=A + C^2**R**-A= C^2 + or - sqrt(**R**-A) =C C=sqrt(**R**-A) or C=-sqrt(**R**-A)2 Answers · Science & Mathematics · 30/08/2007

**r**is rational, so**r**= a / b for some integers a and b, where b is not zero...b^2 = 1 This implies b = 1 or = -1 Since**r**= a / b, it is the case that**r**= a / 1 = a or**r**= a / -1 = -a...1 Answers · Education & Reference · 30/09/2011

**R**= 1.1926, -4.1926 Try using MathWay.com Hope this helps!4 Answers · Science & Mathematics · 07/04/2013

The -

**R**was the original format of the DVD created, and created... had to make the name different somehow, so the went with +**R**. They were originally intended for computers and not...3 Answers · Computers & Internet · 24/07/2008

∑ _{

**r**=1, n} 1= n ∑ _{**r**=1, n}**r**= (n+1)·n/2 ∑ _{**r**=1, n} r²= n·(n+1)·(2n+1)/6 ==>...2nr +r² -n -**r**) = (n²-n)·∑ _{**r**=1, n} 1 + (2n-1)· ∑ _{**r**=1, n}**r**+ ∑ _{**r**=1, n} r² = (n²-n)·n + (2n-1)·(n...1 Answers · Science & Mathematics · 26/07/2009

**R**=4x^2+8x C=x^2+2x**R**-C= 3x^2+6x (**R**-C)'= 6x+6 (**R**-C)"= 6 Now (**R**-C...2 Answers · Science & Mathematics · 13/09/2013

**r**^2+3r-2 = 0 Factorize the equation. then (**r**+1)(**r**-3) = 0 Therefore,**r**= -1 & 33 Answers · Science & Mathematics · 14/10/2008

**R**' or also known as**R**-prime can, but doesn't always have to be the original**R**. It's there to show you that you can place any other alkane substitute in that...3 Answers · Science & Mathematics · 24/04/2010

0.2 +

**r**= 0.2r − 0.06 + 0.3r Fist, let's simplify the right side side:**r**+ 0.2 = 0.5r − 0.06 Next, isolate**r**and simplify. (**r**+ 0.2) - 0.5r - 0.2...12 Answers · Science & Mathematics · 16/10/2007